Out-of-sample validation of the external and internal Migration Propensity Index (MPI) in Honduras - Ceballos, Francisco; Hernandez, Manuel A. (International Food Policy Research Institute, 2025)
The external and internal Migration Propensity Indices (e-MPI and i-MPI) are tools to objectively estimate the probability that individuals from a given household will, respectively, migrate abroad or migrate domestically in the near future. We use new longitudinal data to test their predictive performance fully out of sample. We find that households classified as being of high-propensity to migrate by the e-MPI were significantly more likely to migrate abroad within 24 months (10.7%) than medium- and low-propensity groups (8.8% and 5.3%). For domestic migration, the i-MPI shows an even stronger gradient (19.6% versus 8.5% and 3.5%, respectively). Regression models confirm that both indices outperform alternative predictors—including income, climate shocks, crime, and migration intent—and maintain predictive power across rural and urban areas. Placebo tests indicate that the e-MPI and i-MPI capture distinct dimensions of migration behavior, validating their use for targeting and monitoring migration-related interventions. Overall, the MPIs emerge as simple yet statistically robust tools that reliably predict both international and domestic migration, offering a practical and scalable solution to help governments and development agencies anticipate migration trends and allocate resources strategically.